The Center for Creative Leadership handbook of coaching in organizations - Riddle, Douglas Duane Jacobs, 1949-; Hoole, Emily R., 1968-; Gullette, Elizabeth C. D., 1969- (San Francisco, CA : Jossey-Bass, A Wiley Brand, 2015)
"From coaching superiors to coaching business teams, this book outlines the Center for Creative Leadership (CCL) approach to professional coaching to help readers better manage leadership development and talent management program outcomes. With expert guidance on the key functions of human resources, learning and development, and organizational development, readers will gain insight into the issues associated with coaching program implementation and management, and the use of internal versus external coaches. Coverage includes a wide range of coaching-based services used in most large organizations, with practical advice on creating the right programs for maximum impact within the available budget."--
Part 1: Toward a Coaching Culture -- Chapter 1: The Rise of Coaching in Organizations -- Chapter 2: Assessing Your Organization's Need for Coaching -- Chapter 3: Creating an Integrated Coaching System -- Chapter 4: Evaluating Coaching Interventions -- Chapter 5: Managing Coaches -- Part 2: Coaching Guidance for HR Leaders -- Chapter 6: Coaching the Derailing Leader -- Chapter 7: Developing High-Potential Leaders -- Chapter 8: Coaching at the Top -- Chapter 9: Coaching Your Business Partner -- Chapter 10: Cross-Cultural Coaching -- Chapter 11: Coaching in Context: The Individual in Relation to Organizational Culture -- Chapter 12: Ethical Considerations for the Human Resource Coach -- Part 3: Special Applications of Coaching -- Chapter 13: Coaching for All: Creative Leadership Conversations with Peers -- Chapter 14: Mentoring for Leadership Development -- Chapter 15: Executive Coaching for Onboarding -- Chapter 16: Team Coaching -- Chapter 17: Senior Team Coaching -- Chapter 18: Transforming Organizations: Coaching and Guiding Senior Teams -- Chapter 19: Coaching beyond the Organization
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Executive coaching; Leadership; Mentoring in business; Employees -- Coaching of; Leadership; Accompagnement de gestionnaires; Leadership; Mentorat dans les affaires; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Employees -- Coaching of; Executive coaching; Leadership; Mentoring in business